Prevalence of joint pain and swelling complaints among children of Bashkortostan Republic according to an epidemiological examination - V A Malievsky; R N Valeeva; G E Alexandrova; E N Kostromina; A V Gaisina; L F Musina-Smirnova; A F Husainova (Научно-практическая ревматология)
Objective. To study prevalence of joint pain and swelling among children of Bashkortostan republic (BR). Material and methods. A questionnaire study was conducted in 2 cities and 4 country districts of BR. A questionnaire developed by the Institute of rheumatology of RAMS and adapted for children was used. 43907 children aged 0 to 17 years were included. Results. 5490 children and/or their parents (12,5%) reported joint pain, 754 children (1,7%) - swelling. In general pain and swelling were revealed in 5533 children (12,6%). Joint pain and swelling prevalence was higher in urban than in country population. Joint pain predominated in girls, swelling - in boys. Swelling and pain frequency increased with age. It reached maximum by adolescence (12-17 years) but differences in joint pain frequency between children aged 12 to 14 and 15 to 17 were not statistically significant. Conclusion. Joint complaints (pain and/or swelling) are quite frequent among children and adolescents (12,6%). At present the second phase of the study is being conducted: advanced clinical, laboratory and instrumental examination of children having joint symptoms.